Staged hip replacement for neglected bilateral Crowe’s Grade 4 dysplasia - Al-Otaibi, Mohammed Lafi (International Journal of Health Sciences, 2022)
Factors such as consanguinity, breech presentation, and family history have been attributed to the diagnosis of developmental dysplastic hip (DDH) in Saudi Arabia. The prevalence of DDH in Saudi Arabia is higher in females than in males, with 10.46 cases per 1000 live births. Cases with bilateral high hip dislocation rarely cause early symptoms and can easily be neglected; therefore, these cases present later in life with degenerative osteoarthritis requiring a challenging hip replacement. This report presents the case of a 54-year-old female with bilateral high dislocated dysplastic hip joints. A successful staged bilateral total hip replacement resulted in painless and stable hip joints. The surgery was conducted successfully by ensuring the availability of personnel with the necessary skills, equipment, and an experienced treatment team. Therefore, the results stress the need to utilize screening tests for the early diagnosis and treatment of developmental dysplastic hip.